Synthesis of New Heterocyclic Compounds Derived From 5,10- dihydrophenophosphazine - Al – Araji, Suad M.; abood Gban, Moayad (Iraqi Journal of Science, 2023)
This work comprises the synthesis of 18 new N- substituted 5,10-dihydrophenophosphazine.The diphenylamine was chosen as the starting material ,which was reacted with phosphorus trichloride at elevated temperature (200-220)0Cfor 6 hrs, followed by treating the reaction mixture with water to yield 5,10-dihydrophenophosphazine-10-oxide(1), this was reacted with ethylchloroacetat toobtain ethyl(5,10-dihydrophenophosphazine-10- oxide)acetate(2). Compound (2)was converted to acid hydrazide by treating with hydrazine hydrate( 98% ) to obtain5-(5,10-dihydrophenophosphazine) acetohydrazide-10-oxide (3). The acid hydrazidwas used to react with phenylisocyanat , phenylthioisocyanat to give (4,7)respectively which were used to prepare different heterocyclic compounds.Compound (5) was performed by the intramolecular cyclization of (4) in thepresence of NaOH(2N).Compound (8) was synthesized by interaction of (7) withNaOH(2N).Compound (6) and (9) were obtaind upon the reaction of semicarbazide(4) and thiosemicarbazide (7) with phosphoric acid at 1200C.Compound (3) undergoes the character condensation reaction with differentaromatic aldehyde in ethanol gave the shiff bases (10-18).